2012
DOI: 10.1371/journal.pone.0041574
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA-195 and -451 Regulate the LKB1/AMPK Signaling Axis by Targeting MO25

Abstract: BackgroundRecently, MicroRNAs (miR) and AMP-kinase (AMPK) have emerged as prominent players in the development of cardiac hypertrophy and heart failure. We hypothesized that components of the adenosine monophosphate-activated kinase (AMPK) pathway are targeted by miRs and alter AMPK signaling during pathological cardiac stress.Methodology/Principal FindingsUsing a mouse model of hypertrophic cardiomyopathy (HCM), we demonstrated early elevation of miR-195 and miR-451 in HCM hearts, which targets MO25, a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…35 Also, it is reported that miR-451 levels are significantly increased in the hearts of a hypertrophic cardiomyopathy mouse model and are involved in Cab39 expression in C2C12 cells. 18 However, other unrecognized direct targets of miR-451 may be involved in diabetic cardiomyopathy because growing evidence suggests that miRNAs have large numbers of direct targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Also, it is reported that miR-451 levels are significantly increased in the hearts of a hypertrophic cardiomyopathy mouse model and are involved in Cab39 expression in C2C12 cells. 18 However, other unrecognized direct targets of miR-451 may be involved in diabetic cardiomyopathy because growing evidence suggests that miRNAs have large numbers of direct targets.…”
Section: Discussionmentioning
confidence: 99%
“…These data were consistent with those in a previous report. 18 Thus, we attempted to investigate miR-451 functions in cardiac myocytes.…”
Section: Mir-451 Expression Is Induced By Palmitic Acid Stimulation mentioning
confidence: 99%
“…In this study, we first demonstrated the deregulated expression of circulating miR-130a and miR-451 in DLBCL. According to the results of other studies, miR-451 is a significant anti-oncomiRNA in colorectal carcinoma, and promoted PI3k/AKT and LKB1/AMPK activation by repressing the mitogen-activated protein kinase (MAPK) signaling pathway, and caused an decreased in self-renewal, tumorigenicity and vascular endothelial cell proliferation (33,34). In accordance with the above results, we also detected reduced miR-451 expression, which confirmed the function of miR-451 as a oncogene in DLBCL for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-451 promotes glioma cell adaptation to metabolic stress through suppression of the LKB-1-associated protein CAB39 and indirect activation of mTOR signaling [113]. Recently, miR-195 has been found to also target CAB39 and regulate mTOR [114].…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%